Negotiating Business Narratives Fables of the Information Technology, Automobile Manufacturing, and Financial Trading Industries - Borins, Sandford (Springer International Publishing, 2018)
This book challenges the widely-held belief that popular narratives about business are invariably critical. It develops a more nuanced analytic model of private sector narrative and applies it to 63 recent narrative texts (movies, histories, biographies) produced in the US dealing with three major industries: information technology, automobile manufacturing, and financial trading. It identifies recurring patterns to compare sectors and to analyze their implications. Negotiating Business Narratives appeals to academics and practitioners interested in business and society, strategic management, and contemporary literature and films about business.